Analisa Seat Trunnion tidak Bisa dipasang Spring di PT. XYZ - Reza Dzakaria Imam Lutfi; Deri Teguh Santoso (Jurnal Serambi Engineering, 2024)
PT. XYZ is a company consisting of several departments, one of which is machining and assembly. The ongoing industrial developments make companies compete to innovate the best in order to survive and compete with similar companies. Consumers will have morechoices in choosing products because there is more competition in the business world. Therefore, in order to remain competitive and be able to survive longer than competition with other products. The purpose of this research is to determine various types of defects, the causes of defects, and provide replacement suggestions for improvement. The research results show that there are types of defects in the trunnion parts on the assembly line. Based on the fishbone diagram, the factors that cause product defects are human, machine and method factors. The proposal given in this research is to make parts or make tools such as the Go Nogo Jig Dummy Spring on a conveyor machine that is attached.